(untitled) (Journal of Oriental Studies, 2022)
The article deals with the ethical philosophy of Abu Nasr al-Farabi. The difference between al-Farabi and other thinkers, not only in the creation of his own ethical system, but also he was one of the gifted individuals who implemented these lofty ideas (a perfect philosopher, an exemplary leader, morality, ethics, morality) in his personal life. According to the scientist, beauty is the harmony of a person’s spiritual and physical beauty. The ruler is the leader of a person with ethical and aesthetic beauty. It is received by kind, caring and happy citizens. If they form a people, then it is a virtuous city. The author claims that al-Farabi used the terms “philosopher”, “first leader”, “ruler”, “legislator” and “imam” in the same sense. According to al-Farabi, each of these persons meet the requirements of ethics. To reveal the topic, the researcher analyzes the assertion of the scientist in the ethical system that “a person needs a teacher who leads to happiness.” The goal of human life is to achieve the highest happiness. The person shows the way and explains what happiness is – a mentor. The article uses “Civil policy”, “On the achievement of happiness”, “On the views of the inhabitants of a virtuous city” and other works of al-Farabi in Arabic. Key words: Al-Farabi, Ibn Sina, Al-Ghazali, ethics, morality, philosophy, perfect man, civil society, virtuous city, leader, teacher, moral values.